Pengaturan Waktu dan Teknik Pemanenan Buah Mangga Arumanis - Yuniarti Yuniarti; Suhardjo Suhardjo (agriTECH, 1997)
A study was conducted to determine the most suitable time and technique of harvesting to give sap free mango. The experiment was designed in a factorial randomized block with the first factor was time of harvesting (at 6.00, 8.00, 10.00, 12.00, 14.00 and 16.00 o' clock), while the second factor was technique of harvesting (cutting fruit stalk at the stalk-end, cutting fruit stalk using bamboo basket, cutting fruit stalk at abscission zone, at 1 cm above abscission zone, at 5 cm above abscission zone). Result showed that there was no interaction between time and technique of harvesting and the amount of sap coming out at the first five minutes after fruit stalk cutting. But separately, time or technique of harvesting influenced the amount of sap coming out. Harvesting at 6.00 and 8.00 o'clock gave the largest amount of sap which was significantly different compared to the other treatments. The most suitable time for harvesting was at 10.00 or here after. Technique of harvesting by cutting fruit stalk at abscission zone or at the above resulted the smallest sap amount which was significantly different compared to the others.